Nivel de desempeño en aula de docentes que participaron y no participaron en el programa de capacitación convenio UNE - Callao - Cárdenas Olaguibel, Gabriela Dora (2010)
Research on the level of performance of teachers and non-participants in the Teacher Training Program in Master Agreement UNE - Callao Region took place in public educational institutions in Callao district. The analysis focuses on the evaluation of teaching performance in the classroom in order to verify the training received through master agreements on free and if the evidence of a change in classroom performance. The comparative study - descriptive purposive sample was taken from the database of teachers graduated from the first and second master's training agreement at the National University of Education Enrique Guzmán y Valle. A sample of 66 teachers from four schools in the district of 7Callao worked with four instruments and compared the results of the professors in the classroom. In this regard the evidence showed that no significant differences between those who participated and those who did not. It is necessary to review the programs offered by the Region, verify their achievements through a monitoring to an assessment of achievements, meet the skills and knowledge of our children and youth. Region's investment in education should be evident in substantial changes from teacher training, to implementation in the classroom.